Catholic Church. Province of Cebu (Philippines) records - Catholic Church. Province of Cebu (Philippines)
Ecclesiastical court records of the Bishopric of Cebu.
Collection material in Spanish.
Keywords: Catholic Church -- Philippines; Cebu (Philippines : Province) -- Religion